Pemanfaatan Inokulum Feses Sapi Dalam Uji Kecernaan In Vitro ADF dan NDF Rumput Gajah (Pennisetum purpureum) - alwi, yun (Fakultas Peternakan Universitas Jambi, 2009)
The aim of this study was to reveal the effect of faecal inoculum on the in vitro digestibility of acid detergent fibre (ADF) and neutral detergent fibre (NDF) of Napier grass(Pennisetum purpureum). The design of this reserach was Completely Randomized Design (5 x 4) with five treatments and fourreplications. The treatments were rumen liquor inoculum, faecal inoculum (FI), FI added with sugar of 2.5 % (w/v), FI added with sugar of 2.5 % (w/v) and urea of 2.5 % (w/v) and FI added with urea of 2.5 % (w/v) for treatment A, B, C, D and E respectively. Samples of Napier grass were tested by the two stepin vitro technique of Tilley and Terry (1963). Results of this study showed that faecal inoculum significantly (P<0.05) decreased the digestibility of ADF and NDF of Napier grass. The use of faecal inoculum (treatment B, C, D and E) showed the lower digestibility of ADF and NDF than using therumen liquor. In conclusion,Â the addition of sugar or and urea in the faecal inoculum could not increase the digestibility of ADF, NDF and gas profile of Napier grass.